A multifunctional substance P-conjugated chitosan hydrochloride hydrogel accelerates full-thickness wound healing by enhancing synchronized vascularization, extracellular matrix deposition, and nerve regeneration. (14th May 2021) - Li, Hao; Li, Mengna; Liu, Pei; Wang, Kaiyang; Fang, Haoyu; Yin, Junhui; Zhu, Daoyu; Yang, Qianhao; Gao, Junjie; Ke, Qinfei; Yu, Hongping; Guo, Yaping; et al.
Abstract : The CSCl–SP hydrogel is a multifunctional platform with an ideal capacity to dramatically promote full-thickness wound healing by enhancing angiogenesis, extracellular matrix deposition and remodelling, and nerve fibre growth. Abstract : Due to the native skin limitations and the complexity of reconstructive microsurgery, advanced biomaterials are urgently required to promote wound healing for severe skin defects caused by accidents and disasters. Accumulating evidence has supported that substance P (SP) has a potential effect on skin regeneration. However, SP application is seriously impeded by its poor stability and oxidative reactions occurring during production, transportation, and storage. An SP-conjugated chitosan hydrochloride hydrogel (CSCl–SP) fabricated in this study demonstrated an enhanced capacity to repair full-thickness skin defects. CSCl–SP provided a stable in vitro delivery system for SP. The dissolution of CSCl–SP promoted the proliferation, migration, and tube formation, as well as angiogenesis-related gene and protein expression in human umbilical vein endothelial cells. CSCI-SP also stimulated the proliferation, migration, and production of anabolic growth factor in human fibroblasts. Moreover, CSCl–SP significantly promoted the neurite outgrowth in Neuro-2A cells. In vivo, CSCl–SP dramatically strengthened the vascularization, extracellular matrix deposition and remodeling, and nerve regeneration, thereby promoting efficient recovery of the full-thickness skin defect. Thus, synchronized multifunction of the CSCl–SP hydrogel makes it a promising and smart material for intractable skin defects.